MODEL PELATIHAN UNTUK MENINGKATKAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR - Fadriati Fadriati (Ta'dib, 2020)
Abstract: One of the problems in educational sector in Indonesia today is the low competence of   Elementary School Islamic Religious Education teachers in their instruction. Therefore, efforts to increase their competence need to be realized. One of the efforts can be pursued through quality education and training programs. This research is aimed at producing a training model for    education and teacher training provider and finding out the level of validity of the developed model in improving the competence of Elementary School Islamic Religious Education teachers. The type of the research is R & D which applies Gall and Borg development model. Data sources are training implementers at the teacher training agency of West Sumatera Regional Religious Education Center (Balai Diklat Keagamaan Wilayah Sumatera Barat)  in Padang, namely: the Head of Division of Elementary School Islamic Religious Education (Kepala Bidang PAI SD), and he Head of the Sumatera Regional Religious Education and Training Center in Padang, and the PLPG Implementation Committee for   Elementary School Islamic Religious Education teachers at the Tarbiyah Faculty and Teacher Training Center of IAIN Imam Bonjol Padang. Data were collected through observation, interview, Focused Group Discussion, and expert judgment and questionnaires. Qualitative data were analyzed with the interactive model of Miles and Huberman. Quantitative data were analyzed with descriptive statistics.       The research results showed that the education and training for teachers refers to the centralized model guide The results of the validation of the training model were 80.07% with a very valid category.  Abstrak: Salah satu permasalahan dunia pendidikan di Indonesia saat ini adalah masih rendahnya kompetensi guru PAI SD dalam melaksanakan pembelajaran sesuai kebutuhan. Oleh sebab itu,  upaya-upaya peningkatan kompetensi  pendidik  perlu dilakukan. Salah satu upaya dimaksud dapat ditempuh melalui program pendidikan dan pelatihan (diklat) yang berkualitas. Penelitian bertujuan untuk menghasilkan model pelatihan bagi lembaga pelaksana Pendidikan dan pelatihan guru dan mengetahui tingkat validitas model dalam  meningkatkan kompetensi guru PAI SD. Jenis penelitian yang digunakan adalah R & D dengan menerapkan model pengembangan Gall and Borg. Sumber data penelitian adalah pihak pelaksana pelatihan pada instansi pelaksana pelatihan guru, yaitu: Kepala Bidang PAI SD,  dan Kepala Balai Diklat Keagamaan Wilayah Sumatera di Padang serta Panitia Pelaksana PLPG bagi guru PAI SD di Fakutas Tarbiyah dan Keguruan IAIN Imam Bonjol Padang. Data penelitian dikumpulkan dengan Teknik observasi, wawancara, Focus Group Discussion, meminta expert judgement dan penyebaran angket. Teknik analisis data kualitatif yang digunakan adalah model interaktif. Miles and Huberman. Teknik analisis data kuanitatif menggunakan statistik deskriptif.  Hasil penelitian menunjukkan bahwa pendidikan dan pelatihan bagi guru mengacu kepada panduan model secara terpusat. Hasil validasi model pelatihan adalah 80,07% dengan kategori sangat valid.